(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The role of women in the medieval Serbia was indeed remarkable. They were engaged in cultural and spiritual activities and took active part in public affairs and political negotiations. They also appeared as female rulers and creators of literary works and took part in cultural events. Some of the women from the ruling and aristocratic families had books translated and transcribed for them, they ordered icons, had churches and monasteries built and oversaw their decoration. The field in which women excelled particularly in the Middle Ages was creative church embroidery. Many important embroidery pieces have been preserved as valuable art works created by women. However, in spite of the obvious interest, a complete study about the women’s role in different fields of creativity in the Middle Ages has not been written yet. This review, dedicated to listing of some of their activities, is conceived as a small contribution in this direction. It indicates the activity of the most important medieval women: Queen Jelena of Anjou, Empress Jelena, Duchess Milica, Jephimia the Nun, Jelena Balšić, and Angelina Branković.